Automated dual-axis solar tracking system based on astronomical equation and global positioning system - Mohd Sidek, Mohd Hasimi (2015)
Currently, solar power generation brings many long term benefits such as low operating cost due to no fuel needed and environmental friendly. In solar technology, the sun energy is captured by using photovoltaic (PV) panel and converts the solar radiation into electricity. To maximize a solar module’s power output the module needs to receive as much direct sunlight as possible. A dual axis solar tracker allows a mounted PV panel to remain perpendicular to incident sunlight, thus maximizing power output. In this research, works are focused to overcome the weaknesses in the current tracking system especially for portable and mobile application. Therefore, this study focuses on designing and developing a portable dual-axis solar tracking system that focuses on portable and mobility purpose. Furthermore, this study proposed an electronic control system with embedded sun’s path trajectory algorithm purposely for maximizing the power generated from the attached PV panel. The tracking system utilizes the GPS module and a digital compass sensor for determining the location and the heading feedback of the system respectively. Moreover, the microcontroller based tracking system is embedded with a PID controller for which will increase the PV positioning accuracy by using the feedback signal of the absolute encoder. Furthermore, the research also analyses and compares the output performance between the fixed-tilted PV panel and the developed portable solar tracking.